Applications Of Neuromarketing Sciences On Digital Marketing Models - A Theoretical Frame Work - et. al., Dr.Devi Premnath, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
There is paradigm shift in the way consumers make their purchases as social distancing defines the new norm. There is an over reliance on the digital medium and both the consumers and the marketers have started to embrace the same. The customers have become more active in social media networking and the change can be observed not only in their lifestyles but also in their attitudes and perceptions. So it becomes really imperative that this new channel that the marketers are going to rely on has to tailor itself according to the vicissitudes. The digital marketing has brought in transformations in the purchase patterns. Purchases are no longer a group function and neither is it made consciously .This individual exercise is controlled by the brain. So an individual’s neurological elements and his brain becomes the deciders in a purchase activity. There is a call for exploring methods that can entice one’s brain and thereby help a brand to perpetually map itself high up in this pivotal organ. This paper highlight’s the unexplored relationship and the dependency of digital marketing models on neuromarketing sciences. Neuromarketing is an emerging field in marketing. This nascent marketing strategy connects the subconscious and the emotional facet of a consumer to a brand by the application of various neurological multipliers. Of late, neuromarketing has gained a lot of credibility that most of the marketers have started to wake up to the promising calls of this technique and to harness its potentiality in the digital marketing medium. This paper attempts to analyze the applications of neurosciences on the customer engagement models on digital media.